Falling [compact disc, unabridged] : a novel - Newman, T. J. (Simon & Schuster Audio, 2021)
There are one hundred and forty-three other passengers on your flight. What you don't know is that your pilot's family was kidnapped. The only way the family will survive is if the pilot follows his orders and crashes the plane. Enjoy the flight.